Explicit solutions of higher dimensional Burger's equations - Xia, Fang-Li; Hashemi, Mir Sajjad; İnç, Mustafa; Ashraf, Pakeeza (Shanghai Jiaotong University, 2022)
Burger's equation is one of the nonlinear evolution differential equations, which is essential from the practical and mathematical point of view. This equation is considered in (2+1), (3+1), and (4+1) dimensions in the current work. With the help of the proposed reduction technique, some first integrals and explicit exact solutions are extracted. The novel reported exact solutions which are in the soliton type and travelling wave solutions, are compared with those found by other researchers in literature. Moreover, to the best of authors knowledge, obtained first integrals by Nucci's reduction method are novel and there is no study about the first integrals of the higher dimensional Burger's equations in the literature. © 2022
Keywords: Exact solution; First integral; Higher dimensional Burger's equation; Reduction method